3D Molecularly Functionalized Cell‐Free Biomimetic Scaffolds for Osteochondral Regeneration - Li, Lan; Li, Jiayi; Guo, Jiamin; Zhang, Huikang; Zhang, Xin; Yin, Caiyun; Wang, Liming; Zhu, Yishen; Yao, Qingqiang (Advanced functional materials, 2019)
Clinically, cartilage damage is frequently accompanied with subchondral bone injuries caused by disease or trauma. However, the construction of biomimetic scaffolds to support both cartilage and subchondral bone regeneration remains a great challenge. Herein, a novel strategy is adopted to realize the simultaneous repair of osteochondral defects by employing a self‐assembling peptide hydrogel (SAPH) FEFEFKFK (F, phenylalanine; E, glutamic acid; K, lysine) to coat onto 3D‐printed polycaprolactone (PCL) scaffolds. Results show that the SAPH‐coated PCL scaffolds exhibit highly improved hydrophilicity and biomimetic extracellular matrix (ECM) structures compared to PCL scaffolds. In vitro experiments demonstrate that the SAPH‐coated PCL scaffolds promote the proliferation and osteogenic differentiation of rabbit bone mesenchymal stem cells (rBMSCs) and maintain the chondrocyte phenotypes. Furthermore, 3% SAPH‐coated PCL scaffolds significantly induce simultaneous regeneration of cartilage and subchondral bone after 8‐ and 12‐week implantation in vivo, respectively. Mechanistically, by virtue of the enhanced deposition of ECM in SAPH‐coated PCL scaffolds, SAPH with increased stiffness facilitates and remodels the microenvironment around osteochondral defects, which may favor simultaneous dual tissue regeneration. These findings indicate that the 3% SAPH provides efficient and reliable modification on PCL scaffolds and SAPH‐coated PCL scaffolds appear to be a promising biomaterial for osteochondral defect repair. The molecularly functionalized self‐assembling peptide hydrogel‐coated polycaprolactone scaffolds provide superior performance for the regeneration of cartilage and subchondral bone simultaneously, offering a reliable and flexible strategy for osteochondral defects caused by osteoarthritis or acute trauma.